(untitled) (Sociologisk Forskning, 2009)
Negotiating experience in the court How do judges assess witness credibility, and how do they proceed to reach sustainable conclusions in a criminal court? This article is based on discussions in four focus groups with lay judges in Swedish district courts. In criminal court trials, a version of an event is generally reinforced if it is confirmed by witnesses. However, if their narratives are too similar, none of them is found trustworthy. The focus group participants agreed that if witnesses were suspected of having discussed their individual experiences of an event and accommodated them into a common story, their testimonies were not considered credible. While testimonies should ideally be untainted by other people’s impressions and opinions, other rules govern the truth of the court. The lay judges appreciated their deliberations, including negotiations on impressions and memories of the trial, and they sometimes adjusted their perceptions in the light of information provided by other members of the court. However, if the lay judges are viewed as witnesses of what takes place in the trial, this gives rise to a paradox: While witness negotiations on experiences are regarded as a means to construct a false or biased story, the same kind of interaction between the judges is considered necessary to establish a consensual truth of what actually happened.